Investigations of Physical Compatibilities of Commonly Used Intravenous Medications with and without Parenteral Nutrition in Pediatric Cardiovascular Intensive Care Unit Patients - Katherine Greenhill; Erin Hornsby; Greg Gorman (MDPI AG, 2019)
Many pediatric intensive care patients require numerous specialized intravenous (IV) medications at various dosages in multiple fluids often with nutritional support. This requires several venous access points due to lack of Y-site compatibility data for combinations of two or more drugs. This project investigated physical compatibilities of intravenous medications: alprostadil, calcium gluconate, dexmedetomidine, epinephrine, norepinephrine, esmolol, furosemide, vasopressin, and milrinone with and without lipid-free total parenteral nutrition (TPN) commonly used in a pediatric cardiovascular intensive care unit (CVICU) patient. Actual drug combinations were evaluated using a simulated Y-site study design. Compatibility was determined based on observational data: odor (change/appearance), evolution of gas, and visual appearance combined with physical or chemical endpoints with predefined acceptance criteria: change in pH (± 1 unit), and turbidity (>0.5 NTU) at eight time points between 0 and 240 min. All binary drug combinations along with the four drug plus TPN combination were found to be physically compatible up to 240 min. The three drug combinations were determined to be incompatible and were not evaluated with TPN. This study demonstrates the utility of simulated Y-site study design to multi-drug combinations and increases the scientific body of knowledge related to medications used in a pediatric CVICU.